Institutional trading during a wave of corporate scandals: “Perfect Payday”? - Bernile, Gennaro; Sulaeman, Johan; Wang, Qin (Journal of Corporate Finance, 2015)
This paper examines the role of institutional trading during the option backdating scandal of 2006–2007. Unlike their inability to anticipate other corporate events, institutional investors as a group display negative abnormal trading imbalances (i.e., buy minus sell volumes) in anticipation of firm-specific backdating exposures. Consistent with informed trading, the underlying trades earn positive abnormal short- and long-term profits. Moreover, the negative abnormal imbalances are larger in magnitude when backdating is likely a more severe issue. Local institutions, in particular, display negative trading imbalances earlier in event-time and earn consistently higher trading profits than non-local institutions. Although we find some evidence of over-reaction following the arrival of information about the backdating scandal, these patterns are short-lived and exclusively due to the activity of non-local institutions. Overall, institutional investors behave as informed investors, particularly in local stocks, during this prolonged period of heightened uncertainty about corporate reporting and governance practices.